Osteosarcoma subtypes based on platelet-related genes and tumor microenvironment characteristics - Shu, Yuan; Peng, Jie; Feng, Zuxi; Hu, Kaibo; Li, Ting; Zhu, Peijun; Cheng, Tao; Hao, Liang (Frontiers in Oncology, 2022)
Background osteosarcoma is a common malignant tumor in children and adolescents. Because of its easy metastasis, patients often show a poor prognosis. Recently, platelets have been shown to be highly correlated with the metastasis of a variety of malignant tumors, but the role of platelet related characteristics in osteosarcoma is still unknown. The purpose of this study was to explore the characteristics of platelet related subtypes and cell infiltration in related tumor microenvironment. Methods we collected the osteosarcoma cohort from TCGA and geo databases, and explored the molecular subtypes mediated by platelet related molecules and the related TME cell infiltration according to the expression of platelet related genes in osteosarcoma. In addition, we also explored the differentially expressed genes among different molecular subtypes and established PPI network. Then we constructed platelet scores by univariate regression and least absolute shrinkage and selection operator (lasso) Cox regression analysis (lasso) to quantify the characteristics of iron apoptosis in a single tumor. Finally, we also predicted potential drugs with therapeutic effects on platelet related subtypes. Results two platelet related molecular subtypes were identified in osteosarcoma, and different subtypes had different prognosis. TME cell infiltration analysis showed the difference of tumor microenvironment between the two subtypes. The results of DEGs enrichment analysis between different subtypes showed that DEGs were significantly enriched in immune related pathways. Then we also established a platelet score model composed of TGFB2, GNG12, KIF21B, ANXA5, GAS6 and MAPK1. Kaplan Meier analysis, ROC curve and multivariate regression results further proved that platelet score was an independent risk factor for prognosis. Based on the DEGs between the high-risk group and the low-risk group, we also predicted 15 drugs that may be helpful for the treatment of osteosarcoma. Conclusion platelet score is a significant biomarker, which is of great significance to determine the prognosis, molecular subtypes, characteristics of TME cell infiltration and the effect of immunotherapy in patients with OS.